Mixed methods evaluation of a self-management group programme for patients with neuromuscular disease and chronic fatigue - Ton Satink; Baziel GM van Engelen; Yvonne Veenhuizen; Maud JL Graff; Alexander CH Geurts; Jan T Groothuis; Maria WG Nijhuis-van der Sanden; Edith HC Cup (BMJ Open, 2021)
Objective To obtain insight into experiences of patients with a neuromuscular disease and chronic fatigue and their healthcare professionals regarding content and delivery of a multidisciplinary outpatient self-management group programme to improve social participation. This will inform future implementation.Design A mixed method study alongside a randomised controlled trial.Setting University hospital, rehabilitation centre and community health centre.Participants 29 patients with a neuromuscular disease and chronic fatigue and 13 healthcare professionals participated in this mixed methods study.Intervention Multidisciplinary group programme, called Energetic, consisted of a 4 months intervention with weekly meetings and covered four modules: (1) individually tailored aerobic exercise training; (2) education about aerobic exercise; (3) self-management training in applying energy conservation strategies and (4) implementation and relapse prevention in daily life.Main measures Quantitative data were collected by a questionnaire measuring patients’ (n=25, all completed the programme) satisfaction with the perceived results, content and delivery of the programme. Qualitative data were collected by individual and focus group interviews to gain insight in the experiences of patients (n=18), next of kin (n=2) and healthcare professionals (n=13) with facilitators and barriers to programme implementation.Results Patients were satisfied with the number and length of the sessions, the different modules and the therapists. Analysis of the interviews led to five themes: (1) the combination of modules makes a complete picture, (2) the programme is physically and mentally intensive, (3) the group setting is valuable, (4) small variations in delivery occur in different settings, (5) therapists are coaches. Suggestions for programme improvement include a combination of face to face and e-health, enhancement of therapists’ skills in guiding group interventions and inclusion of more booster sessions to evaluate and maintain self-management competencies.Conclusions The Energetic programme could be implemented in different healthcare settings and group settings, and a combination of modules proved to be a facilitator for improving self-management.Trial registration number NCT02208687.